A survey of graphs in natural language processing*. (12th October 2015) - NASTASE, VIVI; MIHALCEA, RADA; RADEV, DRAGOMIR R.
Abstract: Graphs are a powerful representation formalism that can be applied to a variety of aspects related to language processing. We provide an overview of how Natural Language Processing problems have been projected into the graph framework, focusing in particular on graph construction – a crucial step in modeling the data to emphasize the phenomena targeted.